On the temperature dependence of H‐Uiso in the riding hydrogen model. Issue 4 (27th May 2014) - Lübben, Jens; Volkmann, Christian; Grabowsky, Simon; Edwards, Alison; Morgenroth, Wolfgang; Fabbiani, Francesca P. A.; Sheldrick, George M.; Dittrich, Birger
<x xml:space="preserve">Abstract</x> The temperature dependence of H‐Uiso in N‐acetyl‐L‐4‐hydroxyproline monohydrate is investigated. Imposing a constant temperature‐independent multiplier of 1.2 or 1.5 for the riding hydrogen model is found to be inaccurate, and severely underestimates H‐Uiso below 100 K. Neutron diffraction data at temperatures of 9, 150, 200 and 250 K provide benchmark results for this study. X‐ray diffraction data to high resolution, collected at temperatures of 9, 30, 50, 75, 100, 150, 200 and 250 K (synchrotron and home source), reproduce neutron results only when evaluated by aspherical‐atom refinement models, since these take into account bonding and lone‐pair electron density; both invariom and Hirshfeld‐atom refinement models enable a more precise determination of the magnitude of H‐atom displacements than independent‐atom model refinements. Experimental efforts are complemented by computing displacement parameters following the TLS+ONIOM approach. A satisfactory agreement between all approaches is found.